Abitur 2013 - Geschichte Prüfungsaufgaben mit Lösungen - Müller, Harald; Größl, Wolf-Rüdiger (Abitur ... Baden-Württemberg Geschichte Gymnasium, 2012)
Stichwortverzeichnis 2004-2012, Abiturprüfung 2012